Deletion of porcine BOLL is associated with defective acrosomes and subfertility in Yorkshire boars. (25th September 2020) - Nosková, A.; Wurmser, C.; Crysnanto, D.; Sironen, A.; Uimari, P.; Fries, R.; Andersson, M.; Pausch, H.
Summary: A recessive sperm defect of Yorkshire boars was detected more than a decade ago. Affected boars produce ejaculates that contain spermatozoa with defective acrosomes, resulting in low fertility. The acrosome defect was mapped to porcine chromosome 15 but the causal mutation has not been identified. We re‐analyzed microarray‐derived genotypes of affected boars and confirmed that the acrosome defect maps to a 12.24 Mb segment of porcine chromosome 15. To detect the mutation causing defective acrosomes, we sequenced the genomes of two affected and three unaffected boars to an average coverage of 11‐fold. Read depth analysis revealed a 55 kb deletion that is associated with the acrosome defect. The deletion encompasses the BOLL gene encoding the boule homolog, an RNA binding protein which is an evolutionarily conserved member of the DAZ (Deleted in AZoospermia) gene family. Lack of BOLL expression causes spermatogenic arrest and sperm maturation failure in many species. Boars that carry the deletion in the homozygous state produce sperm but their acrosomes are defective, suggesting that lack of porcine BOLL compromises acrosome formation. Our findings warrant further research to investigate the role of BOLL during spermatogenesis and sperm maturation in pigs.